#Influenced To Care: Comparing Human And Virtual Influencers In Promoting Eco-Friendly Fashion - Elkashif, Mennatallah (AUC Knowledge Fountain, 2025)
In the era of digital media and rapid advancements in artificial intelligence, a new type of influencer has emerged as a key player in shaping consumer behavior: the virtual or AI influencer. Over the past few years, these influencers have gained significant popularity, prompting major international brands with notable success. As consumer demand for sustainability and eco-friendly products grows, and as brands seek effective channels and message sources to communicate these values, the intersection of virtual influencers and sustainable messaging has created an intriguing research gap, particularly in the fashion industry. Fashion brands, striving to overcome skepticism and accusations of greenwashing around their eco-labeled products, are continually searching for credible channels and message sources. Influencers, with their active and engaged follower bases, have long been a valuable asset for these brands. This study seeks to explore the effectiveness of human versus virtual influencers in promoting sustainable fashion, examining which type of influencer yields better results. The research model investigates the role of influencer-message congruence in influencing consumer engagement and purchase intentions, as well as whether the influencer’s credibility—specifically trustworthiness and expertise—serves as a mediating factor. To address these research questions, the study employs a 2x2 experimental design, manipulating Influencer Type (Human vs. Virtual) and Influencer-Message Congruence (Congruent vs. Incongruent), and targets Generation Z consumers. Data was collected through an online survey, with 311 valid responses, and analyzed using PLS-SEM. The findings reveal significant differences between the two types of influencers in driving post-engagement, with marginal evidence for purchase intentions, depending on congruence. Trustworthiness mediates the relationship between influencer type and consumer responses, while expertise does not significantly mediate purchase intentions. However, both dimensions of source credibility mediate the relationship between influencer type and post-engagement. Additionally, message congruence moderates the relationship between influencer type and source credibility.